Carollia perspicillata: A Small Bat with Tremendous Translational Potential for Studies of Brain Aging and Neurodegeneration - Mark Stewart; Timothy Morello; Richard Kollmar; Rena Orman (Biomedicines, 2021)
As the average human lifespan lengthens, the impact of neurodegenerative disease increases, both on the individual suffering neurodegeneration and on the community that supports those individuals. Studies aimed at understanding the mechanisms of neurodegeneration have relied heavily on observational studies of humans and experimental studies in animals, such as mice, in which aspects of brain structure and function can be manipulated to target mechanistic steps. An animal model whose brain is structurally closer to the human brain, that lives much longer than rodents, and whose husbandry is practical may be valuable for mechanistic studies that cannot readily be conducted in rodents. To demonstrate that the long-lived Seba’s short-tailed fruit bat, Carollia perspicillata, may fit this role, we used immunohistochemical labeling for NeuN and three calcium-binding proteins, calretinin, parvalbumin, and calbindin, to define hippocampal formation anatomy. Our findings demonstrate patterns of principal neuron organization that resemble primate and human hippocampal formation and patterns of calcium-binding protein distribution that help to define subregional boundaries. Importantly, we present evidence for a clear prosubiculum in the bat brain that resembles primate prosubiculum. Based on the similarities between bat and human hippocampal formation anatomy, we suggest that Carollia has unique advantages for the study of brain aging and neurodegeneration. A captive colony of Carollia allows age tracking, diet and environment control, pharmacological manipulation, and access to behavioral, physiological, anatomical, and molecular evaluation.